Counter-Radıcalızatıon At Unıversıty - Hanri Aldino; Bambang Sugiri; Anif Fatma Chawa (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The counter-radicalization program has not yet fully targeted preventive measures, both real and in cyberspace. Especially in universities, to neutralize the radical ideologies of terrorism with a soft approach through education of the national spirit. This problem must receive serious attention, to study and analyze and find the potential of radicalism in universities. Then to study and analyze and find alternatives and models of prevention and eradication of terrorism that are suitable for the university environment. So that it can provide a theoretical study regarding the prevention of criminal acts of terrorism committed by people or groups that develop, especially in change universities. In this study, a sequential mixed methods strategy is used, especially a sequential explanatory strategy. The conclusion of this study is the potential for radicalism in the university environment in the form of absolutism, a fanaticism and an understanding of aggression. So it needs to be minimized so that the understanding of exclusivity and extremism does not complement each other which can cause radicalism and terrorism. Then the alternative model for preventing radicalism in higher education with a soft approach based on law and government and by involving the role of the community in the era of terrorism 4.0. So that the researcher recommends carrying out further studies by measuring the effect of the five potential variables of radicalism on acts of radicalism and terrorism then the role of the community is needed in promoting soft approach techniques, especially in tertiary institutions, given the importance of shared awareness of the community in supporting the spread of radical acts of terrorism.